Kontribusi Para Ilmuwan Muslim Dalam Bidang Ilmu Akuntansi - Warto Warto (Al Maal: Journal of Islamic Economics and Banking, 2020)
The blurring of history in the field of science often occurs. In the 18th century AD Adam Smith wrote an economic theory in the book "An Inquiry Into The Nature and Cause Of The Wealth of Nations" later known that economic theory was adopted from the work of phenomenal cleric Ibn Khaldun, written in his book 'al-Muqaddimah'. The same thing happened in Accounting which has obscured its history by the West. This study aims to explore the historical roots of the contribution of Muslim scientists in the field of Accounting. By using a qualitative descriptive method and historical approach, the results of the study show that Islamic Accounting was developed earlier by Muslims than conventional accounting. Islamic accounting emerged and developed since the time of the Prophet Muhammad around the year 610 AD. Whereas Conventional Accounting was introduced to Lucas Pacioli in 1494 AD. Basics of Sharia Accounting in general have been hinted at in the Koran surah al-Baqarah verse 282 and the sunnahs of the Prophet. The paragraph explains the function and importance of recording transactions, the basics, and their benefits, which are the essence of Accounting. Since the time of the Prophet Muhammad until the time of Khulafaur Rashidin, accounting laws have been applied either on an individual scale, syariah or company, waqf accounting, rights prohibiting the use of assets (hijr) and the state budget. In addition, in that era, the accounting profession was also known as "hafazhatul amwal" (financial supervisor).